Pengaruh Kepemimpinan Transformasional, dan Insentif terhadap Kinerja Pegawai Kantor Kecamatan Mojowarno - Nur Hasanah; Imam Baehaki (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
This study aims to analyze the effect of transformational leadership and incentives on the performance of employees Mojowarno District.This study uses quantitative research methods with the independent variable are Transformational leadership and incentives, while the dependent variable is employee performance. The study location is at the Mojowarno District Office, Jombang Regency with the research time in Jue, July and August 2022. In this study the sample taken was The Tembelang District employees totaling 30 people consisting of 16 civil servant and 14 non civil servant. The research data analysis method used is Multiple Liner Regression with technical descriptive analysis, classical assumption test, t test, f test, and coefficient of determination. The result showed that Transformational Leadership had a positive and significant effect on employee performance in Mojowarno District. Incentives had a positive and significant effect on employee performance in Mojowarno District, and Transformational leadership and incentives simultaneously had a positive and significant effect on employee performance in Mojowarno District.